The Effect Oil Press Candlenut Heating Temperature On The Yield and Quality of Candlenut Oil - Dina Lumbantoruan; Ainun Rohana; Adian Rindang (Universitas Sumatera Utara, 2014)
On Oil Press type candlenut heaters, heating temperature needs to be considered. The temperature determines the quality of the heating product. This study tested various temperature of candlenut heaters on the yield and quality of hazelnut. The study was conducted at the Laboratory of Agricultural Engineering and analysis of was done in Food Chemical Analysis Laboratorium Faculty of Agricultural in December 2013 to February 2014 by using a non-factorial completely randomized design at 50°C, 60°C and 70°C. Parameters measured were water content, free fatty acid and yield. The results showed that the temperature had highly significant effect on water content, free fatty acid and yield. The best treatment was the S3 treatment (70°C) which produced 0,19% water content, 1,09 free fatty acid and 45,1% pure oil. Keywords: candlenut heaters, temperature test, candlenut oil quality.